One-day course on process integration for waste minimisation and production carbon footprint reduction - Abdul Aziz, Raman, Ir. Assoc. Prof. Dr. (The Institution of Engineers, Malaysia, 2013)
Link to publisher’s homepage at http://www.myiem.org.my/